Effect of heavy metals on the readaptive processes in the urinary bladder (Bangladesh Journal of Medical Science, 2018)
Introduction: Heavy metals (HM) are dangerous elements due to their toxicity and prevalence play an important role in the environmental pollution and hazards to health risk. Impact of HM at high concentrations may lead to the failures of urinary bladder (UB) structure and functions. The aim of our study was to determine the readaptive changes in the UB of the rats and effectiveness of vitamin E using after the long-term intake of the HMS mixtures.Materials and Methods: We used mature male laboratory rats which were divided into three series with special experimental conditions after the influence of HM. The detailed analysis of the UB state was performed by using morphometric, spectrophotometric, histological and electron microscopy methods.Results: We had determined that the long-term intake of HM caused the significant increase of their accumulation in the tissue and morphometric changes of UB. Obtained results after the cancelation of the HM effect demonstrate smooth morphological restructuring of the UB wall with the reduction of difference of accumulation and morphometric indicators with control. The adjustment of vitamin E during there adaptation period showed better result recovery and optimization of all parameters, but they haven’t completely returned to normal state.Conclusions: The influence of HMS mixture led to significant negative effect on the UB at all stages of research. However, under the conditions of readaptation the tendency towards a certain stabilization of all indicators was observed, but they didn’t completely pass to the end of the study. The vitamin E using has caused the acceleration and improved the development of readaptive change after HM exposure.Bangladesh Journal of Medical Science Vol.18(1) 2019 p.100-106